Human Herpesvirus 6 Infection Presenting as an Acute Febrile Illness Associated with Thrombocytopenia and Leukopenia - Maja Arnež; Tatjana Avšič-Županc; Tina Uršič; Miroslav Petrovec (Case Reports in Pediatrics)
We present an infant with acute fever, thrombocytopenia, and leukopenia, coming from an endemic region for tick-borne encephalitis, human granulocytic anaplasmosis, and hantavirus infection. The primary human herpesvirus 6 infection was diagnosed by seroconversion of specific IgM and IgG and by identification of viral DNA in the acute patient’s serum. The patient did not show skin rash suggestive of exanthema subitum during the course of illness.